Food and urbanism the convivial city and a sustainable future - Parham, Susan (London ; New York Bloomsbury Academic, 2015)
"Cities are now home to over fifty per cent of the world's population, but the contribution of food to shaping cities is often overlooked. Food matters in designing and planning cities because how it is grown, transported, bought, cooked, eaten, cleaned up and disposed of has significant effects on creating a sustainable, resilient and convivial urban future. The book explores methods for extending the gastronomic possibilities of urban space - from the scale of the table to the metropolis. Using a wealth of examples from cities worldwide, the book explores how physical design and socio-spatial arrangements focused on food can help maintain socially rich, productive and sustainable urban space. Underpinning the book's analysis of food and cities is the view that decisions about a hyper-urban future should recognise the fundamental role of food. Food and Urbanism provides an original and new contribution to food scholarship; exploring some intriguing research questions about the ways that food, urbanism and sustainable conviviality interconnect"-- Provided by publisher.
"Cities are now home to over fifty per cent of the world's population, but the contribution of food to shaping cities is often overlooked. Food matters in designing and planning cities because how it is grown, transported, bought, cooked, eaten, cleaned up and disposed of has significant effects on creating a sustainable, resilient and convivial urban future. The book explores methods for extending the gastronomic possibilities of urban space - from the scale of the table to the metropolis. Using a wealth of examples from cities worldwide, the book explores how physical design and socio-spatial arrangements focused on food can help maintain socially rich, productive and sustainable urban space. Underpinning the book's analysis of food and cities is the view that decisions about a hyper-urban future should recognise the fundamental role of food. Food and Urbanism provides an original and new contribution to food scholarship; exploring some intriguing research questions about the ways that food, urbanism and sustainable conviviality interconnect"-- Provided by publisher.
Machine generated contents note: -- DedicationPrefaceAcknowledgementsList of IllustrationsIntroduction: Food and Urbanism: the Convivial City and Sustainable FuturePart One: Food, Domesticity and DesignThe Paradoxical Kitchen and the Death of DiningThe Garden and Gastronomy Part Two: Gastronomy and Public SpaceFood's Outdoor Room The Gastronomic Townscape Ambivalent SuburbiaConvivial Green Space Part Three: Food Space on the EdgeThe Productive Periphery The Megalopolitan Food RealmDesigning the Critical Food Region Food and Urbanism in a Global Context Conclusion: Food and Urbanism - Making a Resilient City BibliographyIndex.
Dr. Phoebe Zoe Maria U. Sanchez (Recommending faculty) - Bookfair2017
Includes bibliographical references (pages 279-351) and index.
Keywords: Sustainable urban development; Food -- Social aspects; Sociology, Urban; City planning; SOCIAL SCIENCE / Agriculture & Food; ARCHITECTURE / Urban & Land Use Planning; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Human Geography